1985
DOI: 10.1063/1.865392
|View full text |Cite
|
Sign up to set email alerts
|

Particle simulations of the low-α Pierce diode

Abstract: The evolution of small initial perturbations of the uniform equilibrium of the ‘‘classical’’ Pierce diode [J. Pierce, J. Appl. Phys. 15, 721 (1944)] is studied using particle simulations. These simulations have been performed with the new bounded-plasma code PDW1 [Wm. S. Lawson (private communication)] and cover the parameter range 0<α<3π, where α=ωpL/v0. In the linear regime, three stages (initial transit, adjustment, and dominant eigenmode) are distinguished; oscillation frequencies, growth/dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…2 Ͼx i Ј(x i ) 2 , for x i Ͼ1, and Ј(1) 2 , for x i Ͻ1. For a given value of x i , nonlinear solutions can be obtained with an increasing number of peaks and valleys as D increases.…”
Section: ͑21͒mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Ͼx i Ј(x i ) 2 , for x i Ͼ1, and Ј(1) 2 , for x i Ͻ1. For a given value of x i , nonlinear solutions can be obtained with an increasing number of peaks and valleys as D increases.…”
Section: ͑21͒mentioning
confidence: 99%
“…The possibility of deterministic chaos arising in Pierce diodes was revealed in these works. At the same time, numerical simulations, 2,8,10,11 began to provide a comprehensive understanding of the nonlinear behaviour of the system, and contributed to the coming of age of the subject. Recent literature indicates a persistent interest in Pierce diodes, and shows new features ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In this case the system may be described by fluid equations. It was also shown that in a narrow range of Pierce parameter the system may represent chaotic dynamics [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Pierce diode is one of the classical models of plasma microwave electronics [1][2][3][4][5][6][7][8][9]. This distributed model though is rather simple, demonstrates many features of the electron beam dynamics in different real electron devices.…”
Section: Introductionmentioning
confidence: 99%
“…However, topics like nonlinear steady-state oscillations and chaotic behavior of the system have been developed only in relatively recent times. 3,[5][6][7][8][9] In many electronic devices, thermionic cathodes with large curvature are used for practical reasons. 10 In fact, electronic devices with cylindrical and spherical electrodes were called ''Pierce electrodes'' ͑see e.g., Ref.…”
Section: Introductionmentioning
confidence: 99%